Chart of North and South America, including the Atlantic and Pacific Oceans, with the nearest Coasts of Europe, Africa, and Asia, A - Jefferys, Thomas, d. 1771 Green, John fl. 1730-1753 (Jefferys, Thomas d. 1771, 1753)
18th century Copper engraving handcolored with watercolor. Outline color. 1 map on 6 sheets mounted on linen. Relief shown pictorially. Printed along the top border: "A Chart of North and South America, including the Atlantic and Pacific Oceans, with the nearest Coasts of Europe, Africa, and Asia." Printed beneath bottom left border: "Publish'd according to Act of Parliament Feb. 19. 1753. by T. Jefferys Geographer to his Royal Highness the Prince of Wales at the Corner of St. Martins Lane Charing Cross." Printed beneath title above Baffin's Bay is a comparative table showing comparisons of observations of exact geographic locations with dates and names of observers. Printed beneath this table: "From the above Table it appears that the Coast of Asia extends 60 Degrees more East than the Maps & Charts of Moll and 53 more than those of Senex place it; so that they omit a vast extent of country, in like manner they curtail the North West Coast of America 20 Degrees in Longd. and 20 in Latd. so making the distance between the two Continents more than 1000 Leagues when it is less than 100." Printed in the northwest region of North America at latitude 72 degrees north and longitude 125 degrees west: "Messrs. Bellin and Bruckner place erroneously Captn. Behrings Isle, where he was stranded and died, here about, in Lat. 72 degrees Long. 125 degrees and continue the Coast from California thither." Printed beneath a line marking the Polar Circle in the northwest region of North America: "These parts, as yet wholly unknown are filled up, by Mssrs. Buache and Del'Isle, with the pretended Discoveries of Adml. De Fonte and his Captains in 1640." Printed in center of Baffin's Bay: "This noble Discovery was made in Search of a N.W. Passage, by Capt. Robt. Bilot, conducted by Willm. Baffin in 1616 not 22: Neither did Munck ever enter this Bay or give it the Name of Christians Sea as some late Charts and Maps English as well as French would have it." Includes multiple tables throughout map comparing geographic coordinates between observers and dates of observation. Shows routes of various explorers including the dates of exploration and names of explorers such as Bering, Tchirikov, Francisco de Gualle, Mendanna, Magellan, Le Maire and Tasman. Also includes multiple notes on geography, exploration and the work of other cartographers. Within the northern half of the map, includes the Kamchatka Peninsula in Russia, the fabled River of the West on the northwest coast of North America, northern California as "New Albion," Baffin's Bay, Hudson's Bay, New England, Canada, Newfoundland, Nova Scotia, New York Pennsylvania, the Great Lakes, Six Nations, Virginia, New Jersey, Maryland, the Islands of Ferro, England, Iceland, Ireland, Scotland, Spain, and part of France. Of note, most of northwestern North America is left blank. Erroneously depicts Alaska as an island and Greenland as connected to North America. In the southern half, depicts California as "Kalifornia," Florida, Mexico, the Galapagos Islands, the West Indies, Louisiana, and Carolina. Also shows South America divided into Teirra Firma, Guyana, Brasil, Chili, Paraguay, Tucuman, Tierra del Fuego, and Peru. Includes the Solomon Islands, part of New Zealand and part of Australia as well as other islands in the South Pacific Ocean. Shows part of West Africa. Shows major rivers and pictorial mountains. Printed on right side of bottom edge is a key to colors used for various colonial holdings held by the British, the French, the Spanish, the Portuguese, the Dutch, the Danes and the Russians. Prime Meridian: London and Isle of Ferro. Scale c.a. 1:20,000,000. [West 180 degrees-East 20 degrees / North 80 degrees - South 60 degrees]. Thomas Jefferys (c.a. 1710-1771) was one of the most significant English cartographers of the eighteenth century. Working as an engraver, geographer and publisher, he created some of the most important English and American maps of his day. He was appointed Geographer to Frederick Prince of Wales in 1748 and later served as Geographer to George III. One of his first maps is a "Plan of London and Westminster" (1732). His other works include Kitchin's "Small English Atlas" (1749), ""Map of Staffordshire" with Parson and Bowles (1747), engravings for Salmon's "Geography" (1749), a last published edition of Saton's "Atlas" (1752), and "Maritime Ports of France" (1761). Between 1751 and 1768, he published a number of other maps, mainly of America and the West Indies including Fry and Jefferson's "Virginia" (1751), "Nova Scotia" (1755), De Braham's "Carolina"' (1757), "St. Lawrence" by Captain cook (1760), a volume on "Spanish Islands and West Indies' (1762), and "Topography of North America and the West Indies" (1768). He also surveyed and engraved "county maps of Bedfordshire" (1765), "Hampshire" (1766), "Oxfordshire" (1766-7), "Durham and West" (1768), "Buckinghamshire" (1770) and "Yorkshire" (1767-70). Despite his prolific nature, Jefferys found himself bankrupt in 1765. Many of his plates were acquired by Robert Sayer who published much of Jefferys' work in "North American Atlas" (1775), "West Indian Atlas" (1775) and "North American Pilot" (1775). Jefferys later partnered with William Faden who received Jeffreys' shop when he died in 1771 (Tooley 335). John Green (fl. 1730-53, d. 1757) constructed many maps and globes. His name was a pseudonym for Braddock Mead. His works include "North and South America" (6 sheets) for Jefferys (1753) and a second edition of the map in 1768 (Tooley, 262). Robert Sayer (1725-1794) was a publisher and map and print seller who published much of his contemporaries' work including the work of Thomas Kitchin, Belin and d'Anville (Moreland and Bannister, 172). He worked with Philip Overton beginning in 1745 until Overton died in 1751. Sayer then continued to work on his own. He published Rocque's small "British Atlas" (1753), "map of Atlantic" (1757) and "Large English Atlas" (1760). He later collaborated with Herbert and reissued many works by John Senex (?-1740). After cartographer, Thomas Jefferys, went bankrupt, Sayer took some of Jeffreys' assets and with Jefferys published "General topographic map of North America and the West Indies" (1768) and "Middle British Colonies in America" (1768, 1775). In 1770, Sayer was joined by John Bennett. In 1771, Jefferys died and most of his business passed to William Faden while some of his plates stayed in Sayer's hands. Sayer and Bennet then published "General Atlas" (1773), "North American Atlas' (1775), "North American Pilot" (1775-6), "American Military pocket Atlas" (1776), "West India Atlas" (1775), and "Complete Channel Pilot" (1781). In 1781 Bennett retired and then died in 1787. Sayer continued to work on his own until his own retirement in 1792. He then sold his plates and business to Robert Laurie and James Whittle (Tooley, 561). This map was first published February 19, 1753 by Jefferys with the aid of John Green (fl. 1730-1753). Each section of the map seems to be a different size (Wagner, 335, entry 578). Alaska was first discovered and mapped by Russian explorers in the eighteenth century. Peter the Great sent out his Danish captain, Vitus Bering in 1728. Bering left from Kamchatka Peninsula and heading east but had little luck in finding land in America. In 1732, Mikhail Gvozdev saw the eastern coast of the Diomede Islands in what is now modern-day Bering Strait, prompting more exploration. In spring of 1741, the Second Kamchatka Expedition began in which Bering was able to explore the Aleutian Islands. During this expedition, Bering and his fellow commander, Aleksei Chirikov (or Tschirikov), attempted to explored the northwest coast of Alaska. Chirikov had little luck, however, landing at Baker Island and coasting north towards Baranof Island. After an exploration boat from his voyage did not return, he decided to return to Kamchatka. Bering's voyage went worse. He was able to explore a little further south and land at Kayak Island during which time the major naturalist and scientist, Georg Steller, hurriedly conducted research on the island. On his return to Kamchatka, Bering wrecked on what is now modern-day Bering Island and died during the crew's stay on the island. After nearly a year, the remaining crew was able to build a ship from the wreckage of the first ship and sail back to Kamchatka, arriving in September of 1742 (Hayes, 102-5). Source(s): Hayes, Derek. "America Discovered: A Historical Atlas of North American Exploration. Vancouver: Douglas and McIntyre, 2004. Moreland, Carl and David Bannister. "Antique Maps: A Collector's Handbook." New York: Longman Group, Ltd., 1983. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. Wagner, Henry R. "The Cartography of the Northwest Coast of America to the year 1800 Volume 2." Berkeley: University of California Press, 1937.